Pastores Novos em Igreja Antiga Uma análise do fenômeno de transformação da relação entre paradigmas e arquétipos pastorais batistas dos pioneiros a atual liderança na perspectiva da Práxis Social e Religiosa - Rosa, Edvaldo Fernandes (2015)
This is a research that aims to identify and analyze within the universe of Brazilian Baptists religious group established in Brazil for more than one hundred and forty years the relationship between paradigms and archetypes that guided the action of pastors as subjects and main developers pastoral methods that church that within the mission of Protestantism, continues to show growth in the religious landscape since its implementation in land brasilis. Establish the historical trajectory of this group, identifying its beginnings amid Separatism English seventeenth century - the old church - and the paradigms that embraced and followed since then as a hard core in terms of belief and practice, all of which can also be identified in the Brazilian Baptist church and the archetypes developed the Brazilian Baptist pastor. Identify and analyze, from the perspective of the pastor, what were your theoretical and practical assumptions, that is, its practical theology and its pastoral theology through a historical review of professional practice, divided into three historical periods fifty years, identified in generations pastors, through a literature search in texts of missionaries, pastors and American theologians - the pioneers - and pastors and theologians Brazilian Baptists or not, thats your place hermeneutic and somehow dealt with the pastoral ministry Baptist, from the its beginnings to the contemporary, and could provide information enabling typify the Brazilian Baptist minister who therefore is above its historical context. Observe nowadays if these paradigms and archetypes are kept, reaffirmed, transformed and reinterpreted or in praxis of pastors and their churches - the new pastor. Also watch from the defined option, what are the possible impacts on their action nowadays. Through this research, identify the existence of transformation of the relationship between paradigms and archetypes and this transformation manifests as revolutions or disruptions.